ANALISIS KELAYAKAN USAHATANI STROBERI DI KABUPATEN BOLAANG MONGONDOW TIMUR (Feasibility Analysis of Strawberry Farming in East bolaang Mongondow District) - Sheren Tesalonika Watuseke; Agnes Estephina Loho; Martha M. Sendow (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2023)
This study aims to determine the feasibility of strawberry farming and strawberry farming income in East Bolaang Mongondow Regency. This research was conducted for three months, from April to June 2022. Respondent in this study were all strawberry farmers in East Bolaang Mon-gondow Regency. The data used are primary data and secondary data. The data analysis used is farming income, R/C Ratio analysis and Break Even Point Analysis. The results showed that straw-berry farming Income in East Bolaang Mongondow Regency was feasible with an R/C Ratio value of 1.84 and strawberry farming in East Bolaang Mongondow Regency would return.the capital when the strawberries were sold was 3.28 kg/month/100m2 with revenues of IDR 569,250/month/100m2. The net income by strawberry farming in East Bolaang Mongondow Regency is IDR 1,454,906/month/100m2, which means that strawberry farming in East Bolaang Mongondow Regen-cy is feasible and already profitable.